PEMENTASAN TARI REJANG DI PURA DESA, DESA ADAT SIDETAPA KECAMATAN BANJAR KABUPATEN BULELENG : (Perspektif Pendidikan Agama Hindu) - Karismayanti, Komang Tari (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
This study aims to determine the educational values contained in the Rejang Dance Performance at Pura Desa Sidetapa Village, Banjar District, from the perspective of Hindu Religious Education. The Rejang Dance Performance, part of the Galungan and Kuningan holiday series, is routinely held three days after these holidays and is a form of the Dewa Yadnya ceremony. The issues examined in this study are: (1) the procession of the Rejang Dance performance at Pura Desa Sidetapa Village, Banjar District; (2) the didactic function of the Rejang Dance performance at Pura Desa Sidetapa Village, Banjar District; and (3) the Hindu religious education values contained in the Rejang Dance performance at Pura Desa Sidetapa Village, Banjar District, Buleleng Regency. This research was conducted qualitatively by selecting informants through purposive sampling. The theories applied in this study are Religious Theory, Structural Functionalism, Aesthetic Theory, and Ethno-Pedagogy. Data collection methods included interviews and document studies. The research findings revealed that: (1) the Rejang Dance performance at Pura Desa Sidetapa Village, Banjar District, Buleleng Regency, begins with the preparation of ceremonial offerings (banten), followed by a communal prayer ceremony, and then the performance of the Rejang dance—a sacred dance performed by young men and women wearing traditional sacred costumes. This sacred dance complements the Dewa Yadnya ceremony at Pura Desa Sidetapa Village, which is believed to bring blessings to the local community; (2) the didactic functions of the Rejang Dance performance include religious, aesthetic, psychological, sociological, and cultural preservation functions; and (3) the educational values identified are religious, aesthetic, psychological, sociological, and cultural preservation values.